Steller’s sea cow genome suggests this species began going extinct before the arrival of Paleolithic humans - Fedor S. Sharko (Nature Portfolio, 2021)
A newly assembled Steller’s sea cow genome suggests that this marine mammal had low levels of genetic diversity and began to go extinct along the North Pacific coastline much earlier than when the first Paleolithic humans arrived in the Bering sea region.